Pure partial trisomy for long arm of chromosome 9. - Faed, M (1976)
A case of a 4-year-old boy with trisomy of the long arm of chromosome 9 is described (46,XY, der (9), t (9;9) (q32;q12)). The trisomy is probably the result of a translocation of the long arm of the chromosome from one homologue to the other in a parental gonad. The clinical features of the child which include severe developmental retardation, bird-like facies, tapered fingers, and flexion contractures of the legs are similar to those of the few cases described of trisomy of the whole chromosome.